Correspondence. - Metcalf, Margaret; Murray, Anthony; Mills, Tony; Thirkill, Alex; Paine, Jo; Clayton, Averil; Hughes, Gordon; Seery, J. (New Statesman, 2015)
Several letters to the editor are provided on British politics and in response to articles in previous issues, including the articles "The tyranny of mere wealth," Michael Sheen in the May 29, 2015 issue, "Saying the Unsayable” in the May 29, 2015 issue and "The sum of male knowledge," by Jenny Kleeman in the May 22, 2015 issue.